Exceptional diversity of Stefania (Anura, Cryptobatrachidae) II: six species from Mount Wokomung, Guyana - MacCulloch, Ross D.; Lathrop, Amy; Khan, Samir Z. (Phyllomedusa: Journal of Herpetology, 2006)
Six species of Stefania were collected on Mount Wokomung, a tepui in the Pakaraima Mountains of Guyana. This unusually high diversity of Stefania is similar to that found on a neighbouring tepui, Mt. Ayanganna. The two tepuis support slightly different habitats. Conspecific Stefania from the two mountains differ somewhat in body size, toe disc size and colouration. Specimens from Mt. Wokomung are used to expand descriptions and distributions of some species.